VARIABILITY OF CHLOROPHYLL-A DISTRIBUTION AROUND BELITUNG ISLAND WATERS OBSERVED BY AQUA-MODIS SATELLITE DATA - Wisha, Ulung Jantama; Khoirunnisa, Hanah (MAJALAH ILMIAH GLOBE, 2018)
Belitung Island has a strategic geographical location, which is directly bordered with Sumatera and Kalimantan also Karimata and Malacca Straits. Those conditions make the waters productivity being high due to the support from the biogeochemical cycle, nutrient runoff, and upwelling. This study aims to determine the seasonal variability of chlorophyll-a (Chl-a) around Belitung waters. The method used in this study was spatial analysis with IDW (inverse distance weighted) to interpolate the Chl-a surface distribution. Sea Surface Temperature (SST) acquired from Aqua-MODIS were retrieved from NASA (National Aeronautics and Space Administration) and wind data were obtained from ECMWF (European Centre for Medium-Range Weather Forecasts), data were analyzed statistically and spatially. The Chl-a concentration in the northeast monsoon ranged 0.38-3.5 mg.m-3, in the southwest monsoon ranged 0.15-18.7 mg.m-3, and in the transitional season ranged 0.29-9.04 mg.m-3. The Chl-a concentration during southwest and 1st transitional monsoons were higher due to the maximum sunlight intensity stimulating photosynthesis of autotroph biota. The condition of SST is indicating the upwelling event that involves wind-driven motion of dense, cooler, and usually nutrient-rich water towards the ocean surface. Seasonal SST variability ranged 22.6-28.3oC, 27.3-32.1oC, 30.7-32.3oC, and  29.1-32.8oC during northeast, 1st transitional, southwest, and 2nd transitional monsoons respectively. The existence of ENSO (El-Nino Southern Oscillation) contributes to enhance the Chl-a concentration. During ENSO years, the Chl-a concentration was higher than non-ENSO years due to the great impact of ENSO inducing upwelling and higher nutrient availability. Chl-a and SST conditions can be used to predict fishing ground and upwelling area.